Variabilidade genética de três populações de Hypostomus hermanni (Teleostei: Loricaridae) das bacias do rio Ivaí, rio Tietê e rio Sapucaí Mirim - Vieira, Rafael dos Santos (2015)
The genetic variability of Hypostomus hermanni was estimated, using electrophoresis in starch gel from three populations collected in the basins of the rivers Ivai, Tiete and Sapucai, one collected in each location. Eight enzyme systems were analyzed: Aspartate aminotransferase (AAT; E.C. 2.6.1.1), Glucose 6-phosphate isomerase (GPI; E.C. 5.3.1.9), Glycerol-3-phosphate dehydrogenase (G3PDH; E.C. 1.1.1.8), isocitrate dehydrogenase (IDH; E.C. 1.1.1.42), L-lactate dehydrogenase (LDH; E.C. 1.1.1.27), Malate desidrogenase (MDH; E.C. 1.1.1.37), Malate dehydrogenase NADP + (ME; E.C. 1.1.1.40) and phosphoglicomutase (PGM; E.C.5.4.2.2). Three loci were obtained with 07 alleles in the population of H. hermanni Keller River, in Piracicaba River eight loci with20 alleles, and individuals river Sapucai Mirim six loci with 16 alleles, individuals analyzed in three watersheds presented all detected polymorphic loci. The average heterozygosity was 0.0527, in the river Keller population, Piracicaba river, was 1.1742 and river Sapucai Mirim the value was 0.1299. By Identity values and genetic distance, It was revealed that all three populations are genetically very similar to each other.